‘The Political Economy of Non-Recurrence: Navigating National Healing, Institutional Reform & Militarisation in Zimbabwe' - Ndlovu, Mandipa Bongiwe (Department of Political Studies, 2021)
The thesis contextualises the state of transitional justice, elite outlooks and militarisation in Zimbabwe, whilst drawing attention to the complexities of achieving this reality. The study draws from transitional justice, civil-military relations, as well as the political settlements literature as analytical frameworks. Essentially, the study poses two key questions: How does studying transitional justice and elite culture help pre-plan for strategies to professionalise the military and reallocate civic-political duties to citizens should Zimbabwe transition out of authoritarianism? Once achieved, how can this be sustained towards socio-economic development? The study also tackles questions of justice and impunity whilst framing client-patron relations amongst the elite as impediments to progress. Amidst cyclical episodes of violation, the thesis links the denial of justice through amnesties, corruption, and further violence, to the politics of policing memory and trauma. This is analysed within the scope of the late Robert Mugabe regime as well as the current Emmerson Mnangagwa regime – both of which are inherited legacies from the Ian Smith regime. The intricacies of elite networks and accumulation are then laid out, culminating in deliberations on how to navigate prospects for reform, in understanding the politics of non-recurrence when contextualising systemic as well as physical violence. The thesis aims to contribute to ongoing discussions on political leadership, national healing, and institutional reform in Zimbabwe.